PRAKTIK AKAD MUSYARAKAH DAN MURABAHAH PADA KOPERASI SYARIAH DALAM TINJAUAN FATWA DSN MUI (STUDI KASUS DI KOPERASI ABDI KERTA RAHAJA TANGERANG) - Fajeri, Moh; Imdadun, Muhammad; Chaniago, Asdi (Institut Agama Islam Sahid Bogor, 2025)
Sharia cooperatives, as a form of Islamic financial institution, have emerged as an alternative for developing a Sharia-based economy. Musharaka and murabahah contracts are two frequently used contracts in Sharia cooperative business activities. This study aims to analyze the practice of musharaka and murabahah contracts in Sharia cooperatives in light of fatwas issued by the National Sharia Council - Indonesian Ulema Council (DSN MUI), a case study of the Abdi Kerta Rahaja Cooperative in Tangerang. This study employed a qualitative approach, collecting data through in-depth interviews with Sharia cooperative management, cooperative members, and other relevant parties. Secondary data was also collected from related documents and relevant DSN MUI fatwas. The results of the study indicate that first: The implementation of musyarakah and murabahah contract practices in sharia cooperatives in the observation of the DSN MUI fatwa in the Abdi Kerta Rahaja Tangerang Cooperative is normatively in accordance with the standard structure of the elements of the fulfillment of a contract in general, but in substance there are several deviations, namely unequal parties, no deferral when payment is due, a fixed and determined nisbah collection method at the beginning of the contract. Second: the settlement of default by customers (syarik) at the Abdi Kerta Rahaja Tangerang Cooperative prioritizes non-litigation channels, namely deliberation between the cooperative and customers. Overcoming default requires paying off the financing provided by the cooperative. This does not make the Abdi Kerta Rahaja Tangerang Cooperative absolutely halal, because the Abdi Kerta Rahaja Tangerang Cooperative is still accompanied by various practices that are prohibited by Sharia. This condition makes the Abdi Kerta Rahaja Tangerang Cooperative a syubhat in Islamic law. The management of the Abdi Kerta Rahaja Tangerang Cooperative needs to be reviewed through Islamic principles so that it aligns with expectations. This way, the Abdi Kerta Rahaja Tangerang Cooperative can carry out its functions without violating religious rules and potentially become the largest musyarakah and murabahah scheme in the world with the largest number of participants if the Abdi Kerta Rahaja Tangerang Cooperative adheres to Sharia aspects in its management.